Kajian Pencegahan Stunting dengan Model Pendekatan Orang Tua (Parent Approach) : Suatu Komparasi dengan Model Sekolah Orang Tua Hebat (SOTH) - Astuti, Ni Nyoman Sri; Yani, Ristya Widi Endah; Syafriadi, Mei (Universitas Malahayati, 2025)
ABSTRACT Stunting is a global health issue that affects children's growth and development, particularly in developing countries. One of the effective prevention strategies is a parent-based approach, including educational models such as Sekolah Orang Tua Hebat (SOTH). However, the effectiveness of this model compared to other approaches still needs further study.This article is a literature review to analyze the effectiveness of a parent-based approach in preventing stunting.This study uses a literature review method with a narrative approach. The search was conducted through scientific databases such as Google Scholar, Garuda, and ScienceDirect using keywords like